Sarcopenia and Back Muscle Degeneration as Risk Factors for Back Pain: A Comparative Study - Kim, Whoan Jeang (Asian Spine J, 2020)
STUDY DESIGN: Case-control study. PURPOSE: To investigate the independent associations of back pain with sarcopenia and with back muscle degeneration, and to introduce a new risk index for back muscle degeneration. OVERVIEW OF LITERATURE: The Asian Working Group for Sarcopenia recommends diagnosis using handgrip strength, gait speed, and skeletal muscle mass. However, these criteria do not strongly reflect back muscle degeneration. METHODS: Patients who completed a questionnaire on back-pain between October 2016 and October 2017 were enrolled in this study. Appendicular skeletal muscle index (ASMI), cross-sectional area (CSA) index, fatty infiltration (FI) rate of the paraspinal muscles, and lumbar extensor strength index (LESI) were measured and compared between no back-pain and back-pain group. Correlations between LESI and ASMI, CSA index, and FI rate were analyzed. The back-pain group was further divided according to ASMI into sarcopenia and non-sarcopenia subgroups and by our newly developed back muscle degeneration risk index based on correlation coefficients between LESI and CSA index, FI rate. Differences in ASMI, CSA index, FI rate, LESI, and Visual Analog Scale (VAS) score between subgroups were analyzed. RESULTS: The ASMI, CSA index, FI rate, and LESI differed significantly between back-pain and pain-free groups. The LESI demonstrated the strongest correlation with FI rate. There were no significant differences in VAS score and back muscle degeneration index in the back-pain group when divided according to the presence of sarcopenia. However, there was a significant difference in VAS score between back-pain patients when classified according to high and low back muscle degeneration risk index. CONCLUSIONS: We suggest that the degree of back pain is more strongly associated with back muscle degeneration than with sarcopenia. This back muscle degeneration risk index, reflecting both back muscle morphology and function, could be a useful parameter for evaluation of back pain and muscle degeneration.